AB0789 PERSISTENCE IN USE OF BIOLOGIC DISEASE MODIFYING ANTIRHEUMATIC DRUGS TREATMENT IN PATIENTS WITH PSORIATIC ARTHRITIS. (2nd June 2020) - Jin, Y.; Chen, S.; Lee, H.; Landon, J.; Merola, J. F.; Kim, S.
Abstract : Background: Treatment for patients with moderate to severe psoriatic arthritis (PsA) relied on TNF inhibitors (TNFi) for many years. Recent approvals of newer biologics include interleukin (IL) -12 inhibitor ustekinumab and IL-17A inhibitors ixekizumab and secukinumab. Limited up-to-date evidence exists for the comparison of utilization patterns between TNFi and IL inhibitors. Objectives: To compare the persistence on treatment with biologic disease-modifying anti-rheumatic diseases (DMARDs) in PsA patients who initiated TNFi versus IL inhibitors. Methods: We conducted a cohort study using a US commercial insurance database (IBM MarketScan: 2014-2017). We identified patients with PsA by using a validated claims-based algorithm (positive predictive value of 82.4%) which required two PsA diagnosis codes and a prescription dispensing for TNFi (etanercept, infliximab, adalimumab, certolizumab, golimumab) or IL inhibitor (secukinumab, ustekinumab, or ixekizumab). The index date was the 1 st drug dispensing date after the 2 nd PsA diagnosis. We excluded patients with biologic DMARD use at any time prior to the index date. Patients were ≥18 years old on the index date and continuously enrolled in the plan for ≥365 days prior and after the index date. Our study outcome was the change in the initial biologic regimen during the year after the index date. Patients were considered as 'persistent users' if they were still on the index regimen, or 'switchers' if they were on a different biologic at the 365 th date of follow-up. We applied 30 days of gap between dispensing after accounting for the days of supply of each dispensing. For sensitivity analysis, we allowed any gap and determined persistent use at 365 th date less strictly. Results: We identified a total of 3, 180 TNFi initiators and 214 IL inhibitor initiators (Table). Mean age was 52.9 (±11.6) years for TNFi initiators and 50.4 (±11.7) years for IL inhibitor initiators. Using the 30-day gap, there were 37.1% persistent TNFi users and 24.8% persistent IL inhibitor users after 1 year form the index date. 11.1% of TNFi initiators switched to a different TNFi while 4.7% switched to an IL inhibitor. Among IL inhibitor initiators, 6.1% switched to a TNFi and 5.6% to another IL inhibitors. However, in the sensitivity analysis where we allowed a longer interval between the fills/ injections, there were 53.0% persistent TNFi users and 53.7% persistent IL inhibitor users. In other words, IL inhibitor patients had a longer interval between the doses than the recommended treatment intervals on the label. Conclusion: In PsA patients, TNFi initiators were more adherent to the initial regimen than IL inhibitor initiators during 1-year follow-up period. However, the sensitivity analysis indicates that some patients may resume their initial treatment beyond the indicated refill intervals. Further investigations are needed to clarify whether this is due to a better treatment effectiveness or adverse effects associated with IL inhibitors. Acknowledgments: This study was supported by an investigator-initiated research grant from Pfizer. The sponsor was given the opportunity to make non-binding comments on a draft of the abstract, but the authors retained the right of publication and to determine the final wording. Disclosure of Interests: Yinzhu Jin: None declared, Sarah Chen Employee of: After finishing the work for this abstract, she has moved to work for Gilead., Hemin Lee: None declared, Joan Landon: None declared, Joseph F. Merola Consultant of: Merck, AbbVie, Dermavant, Eli Lilly, Novartis, Janssen, UCB Pharma, Celgene, Sanofi, Regeneron, Arena, Sun Pharma, Biogen, Pfizer, EMD Sorono, Avotres and LEO Pharma, Seoyoung Kim Grant/research support from: Seoyoung C Kim has received research grants from AbbVie, Roche, Bristol-Myers Squibb and Pfizer.